Játék és játékosság a szervezetben - Tóth, Rita (Vezetéstudomány / Budapest Management Review, 2022)
According to the dominant logic, the first thing that comes to mind about play is entertainment rather than work. In a workplace context, we generally consider playing as a resource or a tool that can be used to reach organizational goals; however, from a different perspective, play is an open-ended transformative process the outcome (and sometimes the starting point) of which cannot be defined. It is thus of utmost importance to study what other approaches and understandings exist about play that could extend the halo of a phenomenon that is constantly shaping organizational life. The current research explored the complex phenomenon of organizational play by synthesizing and re-organizing the scholarly literature about the topic. The present paper highlights definitional questions and introduces the emerged theoretical streams as well as the integral model of organizational play.